The great fallacy of the accelerated expansion of the universe (International Journal of Scientific Research and Management (IJSRM), 2022)
In the present publication it will be shown that the universe is not expanding at an accelerated rate. The cosmological redshift is explained and calculated for a spherically pulsating universe during the expansion.